Characterization of goat neonatal mortality in northern Morocco and impact of colostrum supplementation - Bahri K.; Raes M.; Chentouf M.; Kirschvinck N.; Hamidallah N. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
This present work aims (1) to characterize neonatal mortality of young goats in northern Morocco in relation with passive transfer of immunity via colostrum, and (2) to test a complementation strategy with commercial colostrum in order to increase kid’s immunoglobulin concentration levels for a better protection against infections. This study was performed between November 2016 and May 2018 in northern Morocco. (1) A group of 1236 newborn kids of Beni Arouss, Northern breed and Northern cross breeds where monitored every 15 to 20 days. Regular weight assessment and blood samples on kids aged between 0 and 14 days were performed. (2) For complementation assay (2017-2018), 65 Beni Arouss goat kids were chosen to receive commercial colostrum. To maintain the mother-young bond, kids were allowed to suckle their mother’s immediately after birth. Then, they received one meal (50 between 150 ml of bottled commercial colostrum) for 3 consecutive days, in addition to maternal milk. Animals of this group were compared to non supplemented Beni Arouss kids living in the same farming conditions (n=81). Results showed a mortality rate in goat kids of northern Morocco of 16%, which was significantly lower in Beni Arouss (8%; p<0.01) and mountainous pastures (11%; p<0.05). Median immunoglobulin levels were significantly lower in Beni Arouss kids (8.20 g/L; p<0.05). Supplementation with commercial colostrum of Beni Arouss goat kids in addition to their mother’s milk did not reduce mortality rate. Mortality occurring between 0-3 days was however decreased (10% versus 31% in non-complemented kids) and immunoglobulin levels were significantly increased (18.95 g/L versus 8.32 g/L in non-complemented kids; p<0.05).
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)